16OSTM10: a new open-shell transition metal conformational energy database to challenge contemporary semiempirical and force field methods. Issue 28 (11th July 2022) - Otlyotov, Arseniy A.; Moshchenkov, Andrey D.; Cavallo, Luigi; Minenkov, Yury
Abstract : A new database, 16OSTM10, containing 10 conformations for each of 16 non-multireference realistic-size open-shell transition metal (OSTM) complexes has been developed. Abstract : A new database, 16OSTM10, containing 10 conformations for each of 16 non-multireference realistic-size open-shell transition metal (OSTM) complexes has been developed. Contemporary composite density functional theory (DFT) (PBEh-3c and B97-3c), semiempirical (PM6 and PM7) and the GFN n -xTB/FF family methods were examined against conventional DFT (PBE-D3(BJ), PBE0-D3(BJ), M06 and ωB97X-V) to reproduce the conformational energies. While good performance is observed for the conventional (the average Pearson correlation coefficient is ρ = 0.91) and composite DFT (average ρ = 0.93), semiempirical and force-field methods should still be used with caution for these challenging compounds. The corresponding average ρ values are 0.53 (PM6 and PM7), 0.75 (GFN1-xTB and GFN2-xTB) and 0.62 (GFN-FF). Accounting for the intramolecular dispersion interactions turned out to be crucial for 4 OSTM complexes bearing bulky substituents in close proximity to each other. The influence of the scalar relativistic effects on the conformational energies is negligible for the considered 3d metal species.